Hepatitis C virus (HCV) RNA profiles among chronic HIV/HCV‐coinfected individuals in ESPRIT; spontaneous HCV RNA clearance observed in nine individuals. Issue 6 (26th October 2016) - Grint, D; Tedaldi, E; Peters, L; Mocroft, A; Edlin, B; Gallien, S; Klinker, H; Boesecke, C; Kokordelis, P; Rockstroh, JK
Abstract : Objectives: Studies have shown that hepatitis C virus (HCV) RNA levels remain stable over time in HIV/HCV‐coinfected individuals taking combination antiretroviral therapy (cART), while spontaneous clearance of HCV RNA during the persistent infection phase has been documented only rarely among those with the CC interleukin (IL)‐28B genotype. This study describes HCV RNA profiles and factors associated with changes over time in HCV RNA levels in the ESPRIT study. Methods: HIV/HCV‐coinfected individuals positive for HCV RNA were included in the study. Follow‐up was counted from the first HCV RNA positive test and censored at the initiation of interferon‐based treatment. HCV RNA and IL‐28B measurements were performed in the same reference laboratory. Random effects mixed models were used to analyse changes over time in HCV RNA. Results: A total of 312 ESPRIT patients were included in the study (151 in the arm receiving subcutaneous recombinant IL‐2 and 161 in the control arm). Most of the patients were white (89%) and male (76%), and they had a median of 5 HCV RNA measurements per person [interquartile range (IQR) 3–6; range 1–9]. Median follow‐up was 5 years (IQR: 2−6 years). At baseline, 96% of patients were taking cART and 93% had undetectable HIV RNA. Mean HCV RNA levels decreased by 13% per year over the study period [95% confidence interval (CI) 8–18%; P < 0.0001]. Baseline HCV RNA levels and the change over time in HCV RNA did not differ by randomization arm ( P = 0.16 and P = 0.56, respectively). Nine individuals spontaneously cleared HCV RNA during follow‐up [IL‐28B genotypes: CC, five patients (56%); CT, four patients (44%)]. Conclusions: HCV RNA levels decreased over time in this population with well‐controlled HIV infection. Spontaneous clearance of HCV RNA was documented in five individuals with IL‐28B genotype CC and four with the CT genotype.